Evaluation of English-Chinese translation criteria for terms that are constantly emerging on the Internet : a study using factor analysis and regression analysis - Tan, Sze Khim (2008)
The research analyses the relationships between the various proposed translation criteria in a non-polemic way. The six translation criteria selected for the analysis are faithfulness, comprehensibility, elegance, accuracy, smoothness and popularity.